UMUMKASBIY VA IXTISOSLIK FANLARNI INTEGRATSIYALASH UCHUN VEB-ILOVALARDAN FOYDALANISH - Orınbetov, N.T. (SCIENCE and SOCIETY, 2024)
This text provides recommendations for the analysis of methods and algorithms that can be used for the most effective integration of web applications into the educational process in order to ensure a deep interaction between general and specialized disciplines. In addition, special attention is paid to the integration of the mobile application with modern technologies such as databases, caching systems and cloud platforms.